2008
DOI: 10.1590/s1020-49892008000700007
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da produção científica em odontologia no Brasil

Abstract: Brazil's scientific output in the field of oral health for the period 2001- 2006 was balanced, with increasing interest in the area of population-based oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
27

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 11 publications
1
16
1
27
Order By: Relevance
“…The study of Leles et al 17 and Dias et al 13 have shown the predominance of in vitro laboratory researches (60.34%) in the field of health in general, however, the results found differed from this study, since researches with humans were more prevalent. The emphasis on studies in humans may be justified by the high predominance of studies with the thematic domain of Epidemiology 1,18,19 The thematic domain most found in research was Epidemiology, corresponding to over half of the total number (60.79%), as was found in the results of Barreto 1 , Egry et al 18 and Barreto 19 who concluded that in Brazil, scientific production in Epidemiology is higher than it is in other countries in Latin America and is growing constantly.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…The study of Leles et al 17 and Dias et al 13 have shown the predominance of in vitro laboratory researches (60.34%) in the field of health in general, however, the results found differed from this study, since researches with humans were more prevalent. The emphasis on studies in humans may be justified by the high predominance of studies with the thematic domain of Epidemiology 1,18,19 The thematic domain most found in research was Epidemiology, corresponding to over half of the total number (60.79%), as was found in the results of Barreto 1 , Egry et al 18 and Barreto 19 who concluded that in Brazil, scientific production in Epidemiology is higher than it is in other countries in Latin America and is growing constantly.…”
Section: Discussioncontrasting
confidence: 82%
“…The literature has shown low frequency of studies of the systematic review type, simple literature review and meta-analysis 13,17 in detriment to studies of the scientific research type, which may be justified by the profile of publication demanded by the main journals in the area because, although the reviews are important for adequate referral of a problem, researches are published with greater frequency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations